The Nurses' Level of Knowledge about Developmental Care - Widiastuti, Yuni Puji; Iqomh, Muhammad Khabib Burhanuddin; Ummaiyah, Rohmatul (Proceedings of the International Conference on Nursing and Health Sciences, 2024)
Babies who receive care in hospital still need stimulation to maximize growth and development. One of the nursing efforts that facilitates the development of babies is the implementation of developmental care which can reduce the incidence of disease, length of stay, stress in babies, as well as increasing nerve growth and development of babies. The aim of this research is to identify the level of nurses' knowledge about developmental care in hospitals. The design of this research is descriptive with a cross sectional approach. The research sample was 37 nurses with a total sampling technique. Data collection uses a questionnaire. Data analysis uses descriptive statistics. The characteristics of the respondents were that the largest age was 30 years with the youngest being 22 years and the oldest being 40 years, the majority of respondents were female, 31 people (83.8%), the majority had a DIII Nursing education, 25 people (66, 6%) and the majority have work experience more than 4 years as many as 29 people (78.4%). The results of the study showed that all respondents had a good level of knowledge about Developmental Care in Hospitals, namely 37 respondents (100%).